Evaluation of yield, nutritional quality, and Se distribution in black-grained wheat and bioavailable Se concentrations in soil under irrigation and Se fertilizer application - Meng, Tianqi; Huang, Shuhua; Yu, Yinghan; Sun, Zhaoxin; Wu, Jun; Akram, Zahid; Zhang, Zhengmao; Liu, Yuxiu (Frontiers in Plant Science, 2025)
In the future, ensuring the food and nutritional security of a rapidly growing population will pose an immense challenge in the future. To enhance crop nutrition and address this challenge, a two-year field experiment was conducted on selenium (Se)-deficient dryland soil; the effects of irrigation after Se ore powder (2160 g·ha−1) (Se2160) application on yield-related traits, nutritional quality, and Se uptake and accumulation in black-grained wheat (BGW) and soil Se availability in soil were investigated. This study aimed to determine whether the combination of Se ore powder application and irrigation enhanced yield-related factors and increased the related nutrient in wheat, thereby achieving biofortification. Irrigation had little effect on the grain protein, amylose, amylopectin, total starch, or soluble sugar content, copper concentration in grains, or the Se translocation factor from the root to grain following Se2160 application, but significantly increased the sucrose content and iron (Fe) concentration in grains. Se was readily taken up by roots of irrigated plants in Se2160-treated soils, resulting in leaf and grain Se concentrations that were 4–7 times higher than in control soils. Se fertigation increased the Se distribution in the leaves and grains of BGW due to its decline in the roots and spike-stalk + glume. Se2160 application significantly increased the grain yield and Fe, zinc, Se and manganese concentrations in grains under water regimes. Bioavailable Se concentrations in the 0–20-cm layer of Se2160-treated soil were significantly decreased by irrigation and increasing irrigation amount, but significantly higher than those of control soils, while those in the 20–40-cm layer were not affected. These findings indicate that Se fertigation enhances grain yield, sucrose content, Fe concentration, and Se accumulation in BGW as well as bioavailable Se concentrations in the 0–20-cm soil layer, effects that are conducive to Se-enriched agricultural production and human health improvement.